2002
DOI: 10.1016/s1074-7613(02)00327-8
|View full text |Cite
|
Sign up to set email alerts
|

Redundant and Alternative Roles for Activating Fc Receptors and Complement in an Antibody-Dependent Model of Autoimmune Vitiligo

Abstract: Complement and Fc receptor (FcR)-positive cells mediate effector functions of antibodies. Antibody-dependent immunity against the melanosome membrane glycoprotein gp75/tyrosinase-related protein-1 (TYRP-1) of melanocytes leads to autoimmune hypopigmentation (vitiligo) in mice. Hypopigmentation occurred in mice deficient in activating FcR containing the common gamma subunit (Fc gamma R gamma(-/-)) and in mice deficient in the C3 complement component. Mice doubly deficient in both Fc gamma R gamma and C3 did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 39 publications
2
44
0
Order By: Relevance
“…This scenario bears similarities to the effector phase of other autoantibody-induced inflammatory diseases, including arthritis (24), vitiligo (25), cryoglobulinemia (26,27), bullous pemphigoid (28), and antiphospholipid syndrome (29). In contrast, the pathogenic effects of autoantibodies in other autoimmune diseases such as pemphigus (30) are mediated strictly by binding to their target Ag and do not involve the complement network.…”
Section: Discussionmentioning
confidence: 85%
“…This scenario bears similarities to the effector phase of other autoantibody-induced inflammatory diseases, including arthritis (24), vitiligo (25), cryoglobulinemia (26,27), bullous pemphigoid (28), and antiphospholipid syndrome (29). In contrast, the pathogenic effects of autoantibodies in other autoimmune diseases such as pemphigus (30) are mediated strictly by binding to their target Ag and do not involve the complement network.…”
Section: Discussionmentioning
confidence: 85%
“…Surprisingly, the effector cells responsible for depigmentation included a Thy1+population (Hara et al, 1995). Recently, the pathogenesis of antibody-mediated vitiligo has been characterized (Trcka et al, 2002). Two redundant and alternative pathways can mediate vitiligo in this model, involving either FcgR or complement systems.…”
Section: Antibody Mediated Autoimmunitymentioning
confidence: 94%
“…It has been reported that tumor-specific T-cell responses critically contributed to successful antibody-based tumortargeting therapy that causes cell death through inhibition of growth signals and Fc receptor-mediated ADCC and/or CDC (Cragg et al, 1999;Clynes et al, 2000;Selenko et al, 2001;Trcka et al, 2002;zum Buschenfelde et al, 2002;Smith, 2003;Gelderman et al, 2004). Agonistic anti-DR5 mAb triggered tumor cell death directly via caspase activation, but also secondarily evoked tumor-specific CTL that could also eliminate anti-DR5-resistant variants .…”
Section: Combination With Other Immunomodulatorsmentioning
confidence: 99%